Evaluation of String of Pearls Locking Plate System for Long Bone Fracture Repair in Dogs - Bidari, Kartik; Jahangirbasha, Doddamani; Kumar, D Dilip; Bhagavantappa , B (Indian Journal of Veterinary Sciences and Biotechnology, 2024)
The study was conducted on 18 clinical cases of diaphyseal fractures of long bones in dogs. The dogs were divided into three equal  groups with six dogs in each group, affected with fractures of the radius, femur, and tibia, respectively. Fractures were diagnosed by  clinical, radiological examination and they were stabilized with 3.5 mm locking String of Pearls plates (7-10 holes) and appropriate  locking cortical screws (16-32 mm). All dogs had an uneventful recovery with minimal complications.
Keywords: Dogs; Long bone fracture; String-of-pearls plate